Occurrence of radon in the Polish underground tourist routes - Jerzy Olszewski; Marek Zmyślony; Małgorzata Wrzesień; Katarzyna Walczak (Nofer Institute of Occupational Medicine, 2015)
Background: There are about 200 underground tourist routes in Poland. There are caves, mines or underground structures. This paper presents the results of the research intended to identify the extent of the occurrence of radon concentrations in underground areas of tourist routes. Material and Methods: We conducted the measurement of periodic concentrations of radon (1-2 months) in the summer using type Tastrak trace detectors. We determined the average concentrations of radon in air in 66 underground tourist routes in Poland. Results: The research results comprise 259 determinations of average radon concentrations in 66 routes. The arithmetic average of the results was 1610 Bqm-3, and the maximum measured concentration was over 20 000 Bqm-3. The minimum concentration was 100 Bqm-3 (threshold method) considering the arithmetic average of the measurements. It was found that in 67% of the routes, the average concentration of radon has exceeded 300 Bqm-3 and in 22 underground routes it exceeded 1000 Bqm-3. Conclusions: Radon which occurs in many Polish underground tourist routes may be an organizational, legal and health problem. It is necessary to develop a program of measures to reduce radon concentrations in underground routes, especially routes located in the former mines. Med Pr 2015;66(4):557-563